Penerapan Pembelajaran Kontekstual untuk Meningkatkan Kemampuan Menulis Paragraf Deskripsi Siswa SDIT Thoyyibah - Anisa Rahmawati; Muhammad Ali Akbar (PT. SORATEKNO PUBSLIHER, 2025)
This study aims to describe the development of descriptive paragraph writing skills among third-grade students at SDIT Thoyyibah Kalikebo through the application of a Contextual Based Learning (CBL) approach. The background of this research is the students’ low ability in writing descriptions, which is indicated by limited vocabulary mastery, inability to construct logical sentences, and weak paragraph structure. The method used in this study is classroom action research conducted over two cycles. Each cycle consisted of planning, implementation, observation, and evaluation stages. The study involved 22 third-grade students in the second semester of the 2024/2025 academic year as research subjects. Data collection techniques included observation and writing tests. The results of the study demonstrated that the contextual approach had a positive impact on improving students’ writing skills. In the first cycle, student learning mastery reached 46%, which then increased to 86% in the second cycle. Additionally, students appeared more active and enthusiastic during the learning process. Thus, the contextual learning approach proved to be effective in enhancing descriptive paragraph writing skills among elementary school students